Optical characterization of molecular interaction strength in protein condensates - Beck, Timon; van der Linden, Lize Mari; Borcherds, Wade M.; Kim, Kyoohyun; Schlüßler, Raimund; Müller, Paul; Franzmann, Titus M.; Möckel, Conrad; Goswami, Ruchi; Leaver, Mark; Mittag, Tanja; Alberti, Simon; et al. (Molecular Biology of the Cell, 2024)
Biomolecular condensates have been identified as a ubiquitous means of intracellular organization, exhibiting very diverse material properties. However, techniques to characterize these material properties and their underlying molecular interactions are scarce. Here, we introduce two optical techniques—Brillouin microscopy and quantitative phase imaging (QPI)—to address this scarcity. We establish Brillouin shift and linewidth as measures for average molecular interaction and dissipation strength, respectively, and we used QPI to obtain the protein concentration within the condensates. We monitored the response of condensates formed by fused in sarcoma (FUS) and by the low-complexity domain of hnRNPA1 (A1-LCD) to altering temperature and ion concentration. Conditions favoring phase separation increased Brillouin shift, linewidth, and protein concentration. In comparison to solidification by chemical cross-linking, the ion-dependent aging of FUS condensates had a small effect on the molecular interaction strength inside. Finally, we investigated how sequence variations of A1-LCD, that change the driving force for phase separation, alter the physical properties of the respective condensates. Our results provide a new experimental perspective on the material properties of protein condensates. Robust and quantitative experimental approaches such as the presented ones will be crucial for understanding how the physical properties of biological condensates determine their function and dysfunction.
CRIS-Team Scopus Importer:2025-02-04